Comparative study of clinical presentation and hematological indices in hospitalized sickle cell patients with severe Plasmodium falciparum malaria - Prasanta Purohit; Pradeep K. Mohanty; Siris Patel; Padmalaya Das; Jogeswar Panigrahi; Kishalaya Das (Elsevier, 2018)
Background: Sickle-cell-gene has a high frequency in malaria endemic regions. In India, though the prevalence of both sickle-cell-gene and malaria are high, no study has been carried out. This study aims to find out the possible differences in hematological and clinical parameters in severe falciparum malaria with respect to sickle cell genotypes. Methods: Five hundred fourteen adults with severe falciparum malaria hospitalized in Department of Medicine, Veer Surendra Sai Institute of Medical Sciences and Research, Burla, between August, 2010 to December, 2014 were included and categorized on the basis of sickle cell genotypes. The hematological parameters were compared by one-way-analysis-of-variance and incidence of sub-phenotypes of severe malaria was compared by χ2 test across the groups. Results: Patients with sickle cell anemia (HbSS) and severe falciparum malaria had lower hemoglobin level compared to patients with normal β-globin genotype (HbAA) and sickle cell trait (HbAS). Most of the hematological parameters were homogeneous in patients with HbAA and HbAS and different from patients with HbSS. Incidence of acute renal failure was low (χ2, 9.91; p, 0.002) and jaundice was high (χ2, 5.20; p, 0.022) in patients with HbSS. No clinical difference was observed in patients with HbAA and HbAS. The mortality was low (χ2, 4.33; p, 0.037) and high (χ2, 10.48; p, 0.001) in patients with HbAS and HbSS respectively compared to patients with HbAA. Conclusion: Though sickle-cell-gene protects against falciparum infections, the hematological parameters and sub-phenotypes of severe malaria remain unchanged when the infection progresses to a severe form in patients with HbAA and HbAS. Presence of hemolytic anemia in patients with HbSS shows diverse hematological and clinical phenotypes as compared to others. High mortality in patients with HbSS emphasizes the need for a better preventive approach to save valuable lives. Keywords: Plasmodium falciparum, Severe malaria, Sickle cell gene, Anemia, Mortality